382. Virulence in Candida glabrata Is Not Attenuated by FKS Mutations but Associated With the Frequency of Cells With Distinct Morphology. (26th November 2018) - Hu, Chenlin; Fong, Gary; Beyda, Nicholas D
Abstract: Background: Echinocandins are the first-line treatment for C. glabrata; however, echinocandin resistance is increasingly reported. Acquired FKS -mediated echinocandin resistance has been associated with the upregulation of chitin synthesis and attenuated fitness and virulence in C. albicans ; however, conflicting data are reported in C. glabrata . Here, the influence of FKS mutations on fitness, virulence, morphology, and cell wall chitin was assessed among clinical strains of C. glabrata . Methods: Three sets of isogenic paired strains consisting of an index-WT and persistent- FKS mutant (S663P), two un-paired FKS mutant strains (S663F and S629P), and a WT reference strain (CBS138) were included. Growth kinetics were measured over 24 hours in 96-well microplate containing liquid RPMI. After overnight growth in RPMI and staining with a chitin-specific fluorescent marker, morphology, and chitin were assessed at the single-cell level utilizing high-content imaging technique. Virulence was evaluated in Galleria mellonella larvae by injecting 10 7 cells/larvae. Mortality was assessed daily for 5 days. Results: Significant differences in growth kinetics, frequency of morphologic phenotypes within the cell populations (nonbudding, single-bud, multiple-buds), and virulence were observed between strains obtained from different patients ( P < 0.05 for each). However, no difference was observed between paired index-WT and persistent- FKS S663P mutants. Compared with index-WT and the CBS138 reference strain, FKS mutant isolates (S663P, S629P, and S663F) had significantly elevated cell wall chitin content ( P < 0.05). Neither chitin content, the presence of an FKS mutation, nor in vitro growth characteristics were found to be associated with virulence. Virulence was strongly correlated with the frequency of multi-bud cells within the population however, with 5-day post-injection survival rates of 4% vs. 28% for high-frequency (>12% multi-bud cells) and low-frequency strains, respectively ( P < 0.001). Conclusion: Acquired FKS -mediated echinocandin resistance induced significant alterations in cell wall chitin content but was not observed to attenuate fitness or virulence. Virulence was highly associated with the frequency of cells with distinct morphology. Disclosures: N. D. Beyda, Astellas: Grant Investigator and Scientific Advisor, Consulting fee and Research grant.